Haematological Guide for Endangered Bargur Breed – The Hilly Cattle of Tamil Nadu - Palanisamy, G; GowriManokari, K. V.; Kumaravelu, K. V.; Subash , R.; Kumar, V. (International Journal of Livestock Research, 2020)
Bargur cattle breed is a medium sized, draught breed of cattle available in Tamil Nadu, India and it is a unique breed well adapted to special type of climatic, nutritional, environmental and pathogenic exposure. The current study was formulated to establish the normal reference haematological range for different age groups of Bargur cattle which were maintained in the TANUVAS-Bargur Cattle Research Station, Bargur, Tamil Nadu, India. In this study, haematological parameters such as Total Erythrocyte Count (TEC) 106/µL, Total leukocyte count (TLC)103/µL , Packed cell volume (PCV) per centage, Haemoglobin concentration (Hb) g/dL , Mean corpuscular volume (MCV)(fl) , Mean Corpuscular haemoglobin (MCH) pg, Mean corpuscular haemoglobin concentration (MCHC) g/dL and platelets 103/µL were estimated with use of Automatic Haematological Analyser for different age groups. The average corresponding values were 8.46 ± 0.42, 11423.08 ± 518.52, 34.40 ± 2.31, 11.15 ± 0.79, 40.89 ± 1.63, 13.31 ± 0.54, 32.62 ± 0.50 and 303785.71 ± 23665.90, respectively, obtained in the present study for adult Bargur cattle. Study results indicated that all the haematological values were under the normal physiological range. These findings of this study may serve as reference values in which alterations due to metabolic, nutrient deficiency, physiological and health status can be compared for diagnostic and therapeutic purposes.